1996
DOI: 10.1046/j.1464-410x.1996.08433.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of ureteric calculi during pregnancy by ureteroscopy and laser lithotripsy

Abstract: Ureteroscopy and laser lithotripsy seem, in experienced hands, to be a safe and reliable method in the treatment of ureteric calculi during pregnancy. Most cases can be treated without using fluoroscopy and in some cases the operation can be performed under local anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Carringer, et al [23] reported four pregnant women (mean age 29.5 years, range 27-35 years) with 5 episodes of ureteric stones who were treated by means of ureteroscopy and laser lithotripsy when the fetus was at 26 to 35 weeks of gestation. The calculi which were between 5 mm and 16 mm in diameter were located in the proximal ureter (1) and distal ureter (4).…”
Section: Published By Sciedu Pressmentioning
confidence: 99%
See 2 more Smart Citations
“…Carringer, et al [23] reported four pregnant women (mean age 29.5 years, range 27-35 years) with 5 episodes of ureteric stones who were treated by means of ureteroscopy and laser lithotripsy when the fetus was at 26 to 35 weeks of gestation. The calculi which were between 5 mm and 16 mm in diameter were located in the proximal ureter (1) and distal ureter (4).…”
Section: Published By Sciedu Pressmentioning
confidence: 99%
“…The calculi which were between 5 mm and 16 mm in diameter were located in the proximal ureter (1) and distal ureter (4). Carringer, et al [23] reported that:…”
Section: Published By Sciedu Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31] Lithoclast and laser were used during ureteroscopy to treat ureteric calculci. 27,31 The risk of primary uretroscopy in pregnancy include a 5% risk for minor abrasions, 32,33 2% risk of perforation and creation of a false passage, 32,33 1% risk of avulsion and stricture formation 32,33 and the risk of preterm labour and delivery.…”
Section: Primary Ureteroscopymentioning
confidence: 99%
“…However, in recent years, many of the reports of URS in pregnant women have also utilized local or regional anesthesia. [2022242628]…”
Section: Treatment Alternativesmentioning
confidence: 99%